CASES OF INDIRECT EXPROPRIATION IN INTERNATIONAL ECONOMIC LAW - LAURA-CRISTIANA SPATARU-NEGURA; MIHAI SPATARU-NEGURA (Challenges of the Knowledge Society)
Unforeseen difficulties arise along with the government measures whose object is not to expropriate or to nationalize the foreign investment, but to deprive the foreign investors of the rights attached to their investments. These measures are generally known as measures of indirect expropriation or nationalization. When asked about what falls into the concept of indirect expropriation, a simple answer can not be given easily, but the circumstances in which these measures may occur can be described and discussed. These measures could be grouped as follows: forced sale of property; forced sales of shares of an investment through a corporate vehicle; indigenization measures; taking control of investment management; determination of others to take physical property; failure to provide protection when there is interference with the foreign ownership; administrative decisions that cancel licenses and permits required for foreign businesses to operate in the host state; exorbitant taxation; the expulsion of the foreign investor contrary to the international law; harassment (e.g. freezing of the bank accounts). This paper therefore argues that in practice there are many situations which may be analysed as measures of indirect expropriation.